Obesity Adversely Affects Survival in Pancreatic Cancer Patients - McWilliams, Robert R. (2010)
PURPOSE: Higher body-mass index (BMI) has been implicated as a risk factor for developing pancreatic cancer, but its effect on survival has not been thoroughly investigated. We assessed the association of BMI with survival in a sample of pancreatic cancer patients and utilized epidemiologic and clinical information to understand the contribution of diabetes and hyperglycemia. METHODS: A survival analysis using Cox proportional hazards by usual adult BMI was performed on 1,861 unselected patients with pancreatic adenocarcinoma; analyses were adjusted for covariates that included clinical stage, age, and sex. Secondary analyses incorporated self reported diabetes and fasting blood glucose in the survival model. RESULTS: BMI as a continuous variable was inversely associated with survival from pancreatic adenocarcinoma [hazard ratio 1.019 for each increased unit of BMI (kg/m(2)), p < 0.001] after adjustment for age, stage, and sex. In analysis by National Institutes of Health BMI category, BMI of 30–34.99 kg/m(2) (HR 1.14, 95% confidence interval 0.98–1.33), 35–39.99 kg/m(2) (HR 1.32, 95% CI 1.08–1.62), and ≥40 (HR 1.60, 95% CI 1.26–2.04) were associated with decreased survival compared to normal BMI of 18,5–24.99 kg/m(2) (overall trend test p<0.001). Fasting blood glucose and diabetes did not affect the results. CONCLUSIONS: Higher BMI is associated with decreased survival in pancreatic cancer. Although the mechanism of this association remains undetermined, diabetes and hyperglycemia do not appear to account for the observed association.